Integrated wideband chip-scale RF transceivers for radar sensing and UWB communications: a survey - Fang, Zhongyuan (2022)
With the rapid development of semiconductor technologies, the wideband transceiver is in the trend to be integrated on-chip with compact size and low power consumption. This survey investigates the integrated wideband chip-scale RF transceivers for radar applications including imaging, multimodal sensing, and recognition on gaits, where frequency modulated continuous wave (FMCW) radar sensors are investigated in detail. Besides radar sensing, integrated wideband RF transceivers for accurate localization and efficient communications with spectrum sharing are discussed, in which the integrated wideband transceiver techniques for ultra-wideband (UWB) communications are highlighted. The compact and efficient antenna designs for integrated wideband RF transceivers are discussed. Furthermore, leveraging the artificial intelligence (AI)-enhanced signal processing techniques, edge devices with energy-efficient integrated RF transceivers can ensure precise localization and realize versatile sensing to empower accurate health status monitoring, intelligent robots, gesture recognition, and enhanced communications. We envisioned the future integrated wideband RF transceiver development trends, where the promising tera-Hertz (THz) integrated transceiver techniques are discussed. Notably, the wideband integrated RF transceiver technique is promising to enable efficient, flexible, and seamless communications and sensing for the future-generation intelligent Internet of Everything (IoE) applications.